MODELLING THE IMPACT OF MINING ON SOCIO-ECONOMIC INFRASTRUCTURE DEVELOPMENT - A SYSTEM DYNAMICS APPROACH - Maluleke, George; Pretorius, Leon (The South African Journal of Industrial Engineering, 2016)
The contribution of mining activities to social infrastructure and human development is a complex socio-economic development issue in South Africa. Complexity theory has introduced a new approach to solving problems in social systems, recognising them as complex systems. The socio-economic development system in South Africa falls into this category of complex systems. Analysing such a system requires that a number of feedback loops and details about the issues be analysed simultaneously. This level of complexity is above a human’s ability to comprehend without the aid of tools such as systems thinking and system dynamics. The causality between investment in infrastructure capacity and socio-economic development is dynamic. The relationship is influenced by exogenous feedback that, if not managed, is likely to reverse itself. This paper presents the results of a system dynamics modelling of the relationship, based on the principle of relative attractiveness developed in previous system dynamics research. A Monte Carlo analysis is used to determine the sensitivity of the system to changes in feedback. The paper concludes that the limits to growth in a socio-economic environment are determined by more factors than the availability of capital, and also include land capacity constraints and skills shortage.